Konseling Kelompok Teknik Role Playing Untuk Meningkatkan Kepercayaan Diri Peserta didik - Anisahria, Anisahria; Ratu, Bau; Suhrah, Suhrah (Universitas Palangka Raya, 2025)
This study aims to increase students' self-confidence through group counseling services with role play techniques. The method used is Guidance and Counseling Action Research which consists of several cycles, including planning, implementation, observation, and reflection stages. The research subjects were participants who were educated with low levels of self-confidence based on the results of the initial assessment. The role playing technique was chosen because it is able to provide direct experience to participants in dealing with social situations, thus helping them develop self-confidence. The role playing technique in group counseling proved to be effective in increasing students' self-confidence. In cycle I, the average self-confidence increased from 46.9% to 65.1%, with 37.5% of students in the high category and 62.5% in the medium category. In cycle II, the average increased to 71.31%, with 87.5% of students in the high category and 12.5% in the medium category. This increase was characterized by the participants' ability to express opinions, interact with peers, and show a confident attitude in daily activities. These findings suggest that the application of role playing techniques can be an effective alternative strategy in guidance and counseling services. Future researchers are advised to test the effectiveness of this role playing technique on a larger population of students or at various levels of education.